2011
DOI: 10.1186/1743-422x-8-512
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chicken anemia virus genome: evidence of intersubtype recombination

Abstract: BackgroundChicken anemia virus (CAV) is the causative agent of chicken infectious anemia. CAV putative intergenotypic recombinants have been reported previously. This fact is based on the previous classification of CAV sequences into three genotypes. However, it is unknown whether intersubtype recombination occurs between the recently reported four CAV genotypes and five subtypes of genome sequences.ResultsPhylogenetic analysis, together with a variety of computational recombination detection algorithms, was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…3), the recombinant region spanned the partial VP1 region and partial non-coding region. Studies have confirmed that CAV recombination is only found inter-group2324, but our research identified an intra-group recombination event among CAVs, which has not been previously described.…”
Section: Resultssupporting
confidence: 54%
“…3), the recombinant region spanned the partial VP1 region and partial non-coding region. Studies have confirmed that CAV recombination is only found inter-group2324, but our research identified an intra-group recombination event among CAVs, which has not been previously described.…”
Section: Resultssupporting
confidence: 54%
“…This result indicated that different strains of CAV might coinfect a single bird or flock and that might lead to virus recombination (Ducatez et al., ; van Santen et al., ; Snoeck et al., ). Reports from China also showed that new strains of CAV could be generated by inter‐ or intragenotypic recombination, and the recombination region might span the coding and non‐coding regions (Eltahir, Qian, Jin, & Qin, ; He et al., ; Zhang et al., ). In the current study, the CAV DNA was cloned into a plasmid vector before sequencing analysis and the dominant sequence in a sample was easy to be selected for sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the amino acid substitutions at positions 133 and 144 of VP1 can affect the ability of CAV spreading in cell culture (Renshaw et al., ). Moreover, CAV can undergo recombination to generate new genetic variants (Eltahir, Qian, Jin, & Qin, ; He et al., ; Zhang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Different molecular techniques such as polymerase chain reaction (PCR), hybridization assay, restriction enzyme analysis and sequencing have therefore been developed for CAV detection and characterization (Noteborn et al, 1992;Saini & Dandapat, 2009). VP1, the major and the sole structural protein of CAV with the highest variability and also liable for intergenotype and intersubtype recombination events (He et al, 2007;Eltahir et al, 2011a), is the most appropriate component of the virus for molecular characterization.…”
Section: Introductionmentioning
confidence: 99%